An Analysis of Mathematical Connection Ability in Cubes and Cuboids Learning Materials Based on Gender Differences - Hotipah, Putri; Pujiastuti, Heni (Desimal: Jurnal Matematika, 2020)
This study was aimed to describe the students' mathematical connection ability in cube and cuboid learning materials based on gender differences. The research method employed was descriptive-qualitative. This research involved 6 subjects consisted of 3 males and 3 females students. Based on the results and discussion, it can be concluded that the total average score of male students was 54.5% and female students were 63.3%. Based on the categories of ability, male students were in a low category, while female students were in the moderate category. Several factors might cause this to happen, one of which was the low basic mathematical knowledge.